2008
DOI: 10.1073/pnas.0803860105
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic profiles reveal evolutionary relationships within the “twilight zone” of sequence similarity

Abstract: Inferring evolutionary relationships among highly divergent protein sequences is a daunting task. In particular, when pairwise sequence alignments between protein sequences fall <25% identity, the phylogenetic relationships among sequences cannot be estimated with statistical certainty. Here, we show that phylogenetic profiles generated with the Gestalt Domain Detection Algorithm-Basic Local Alignment Tool (GDDA-BLAST) are capable of deriving, ab initio, phylogenetic relationships for highly divergent proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 56 publications
1
35
0
Order By: Relevance
“…These simulations also isolate amino acids which are integral to, and surround the known phosphotyrosine and hydrophobic binding pockets. These data correlate well with the NMR study of Tokonzaba et al (18), which demonstrated that these pockets were involved in binding phosphatidylinositol (4,5) bisphosphate (PIP(4,5) 2 ) by the SH2 domain contained in Abelson murine leukemia viral oncogene homolog 1 (c-abl), a distant relative of Tec kinases (18). Moreover, phylogenetic analysis of Tec kinase SH2 domains indicate that this region is evolving more rapidly than the other homologous domains contained in this family, suggesting this is a site of functional innovation.…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…These simulations also isolate amino acids which are integral to, and surround the known phosphotyrosine and hydrophobic binding pockets. These data correlate well with the NMR study of Tokonzaba et al (18), which demonstrated that these pockets were involved in binding phosphatidylinositol (4,5) bisphosphate (PIP(4,5) 2 ) by the SH2 domain contained in Abelson murine leukemia viral oncogene homolog 1 (c-abl), a distant relative of Tec kinases (18). Moreover, phylogenetic analysis of Tec kinase SH2 domains indicate that this region is evolving more rapidly than the other homologous domains contained in this family, suggesting this is a site of functional innovation.…”
Section: Introductionsupporting
confidence: 88%
“…These profiles can be obtained from any protein-sequence knowledge-base source (e.g. Protein Data Bank (PDB), Pfam, SMART, NCBI Conserved Domain Database (CDD)) (24). In this study, we curated 131 profiles from CDD which are functionally related to peripheral lipid-binding (PLB) (8;17).…”
Section: Resultsmentioning
confidence: 99%
“…A variety of methods have been developed in this area (6,50), often making use of phylogenetic profiles, in which each entry in a vector quantifies the alignment between a specific target sequence and a knowledge base position-specific scoring matrix (PSSM) (18). To date, the results of analyses using these methods have been encouraging, and they do at least as good a job as standard phylogenetic methods based on multiple sequence alignment in revealing key aspects of evolutionary history (6). However, whether they can provide new insights into systems as diverse as different families of RNA viruses, for which multiple sequence alignments fail completely, is another question entirely.…”
Section: How Do We Improve Our Understanding Of Viral Origins?mentioning
confidence: 99%
“…Given this matrix, we calculate the Euclidean distance between all pairs and generate a NXN distance matrix for tree inference. The statistical robustness and computational cost of this initial algorithm did not make it feasible in practice; however, it was sufficiently robust in a benchmark data set of divergent retroelements [8]. This initial success led us to pursue this approach further, and alterations to the initial algorithm are discussed in detail in following sections.…”
Section: Introductionmentioning
confidence: 99%